Pengaruh Digital Leadership, Employee Engagement, dan Psychological Safety terhadap Kinerja Pegawai Perumda Air Minum Tirta Bahari Kota Tegal - Setiawan Firmansyah; Hendri Sucipto; Muhammad Syaifulloh; Akbar Nuur Purnama (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study aims: 1) To test and measure how big the percentage and analyze the influence of Digital Leadership on Employee Performance 2) To test and measure how big the percentage and analyze the influence of Employee Engagement on Employee Performance 3) To test and measure how big the percentage and analyze the influence of Psychological Safety on Employee Performance 4) To test and measure how big the percentage and analyze the influence of Digital Leadership, Employee Engagement, and Psychological Safety on Employee Performance. The type of research used in this study is a quantitative approach, this study has a population of 284 with a sample of 74 respondents. Based on the analysis and discussion, it can be concluded that H1: Digital Leadership has a positive and significant effect on Employee Performance with a t-count value of 2.117> t-table 1.661 and Digital Leadership sig. value 0.038 <0.05, H2: Employee Engagement has a positive and significant effect on Employee Performance. with a t-count value of 0.401 <t-table 1.666 and sig. value. 0.689 > 0.05, H3: Psychological Safety has a positive and significant effect on Employee Performance with a calculated t-value of 4.631 > t-table 1.666 and a significant value of 0.000 < 0.05, H4: Digital Leadership, Employee Engagement, and Psychological Safety simultaneously have a positive and significant effect on Employee Performance with a calculated F-value > F-table (16.349 > 2.73) and a significant value of 0.000 < 0.05, and an influence value of 38.7%.